Pengaruh Penggunaan Model Pembelajaran Problem Based Learning Berbantuan Media Audio Visual Terhadap Keterampilan Berpikir Kritis Mahasiswa Pada Pembelajaran Konsep Dasar IPS di PGSD STKIP Adzkia - Silfi Melindawati; Sry Apfani; Ade Irma Suryani (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The background of this research is that the lecture design is not optimal so that students can think critically in understanding social studies material assisted by audio-visual media. The design of this research is Quasi-Experimental with a Non-Equivalent Control Group Design. The population is the second-semester students of the 2020/2021 academic year. The sampling technique used a saturated sample, Class II C as the experimental class and II D as the control class. Test the hypothesis by t-test and the data obtained by the value of tcount = 1,729 with a difficulty level of 5% with the test criteria if tcount> ttable then H1 is accepted and H0 is rejected. The experimental class test results averaged 74.5 and the control class averaged 65. The standard deviation of the control class (S=19.9) was greater than the standard deviation of the experimental class (S=14,4). The value of t-test is tcount = 1,729 and ttable = 1,686. The results of the study prove that the use of the Problem Based Learning model with the aid of Audio Visual media has an effect on students' critical thinking skills in learning the basic concepts of social studies at Adzkia University.